Dynamics of Dissent and Whistleblowing: Conceptualization and the Way Ahead - de Castro Halis, Denis (Revista Científica do CPJM, 2022)
The dynamics of dissent (e.g. how dissent is formed, channeled, promoted, or stifled) are not sufficiently studied despite their importance in times of profound societal crises. During the 2020 pandemic, for instance, many have dissented to the restriction of their freedoms and rights carried out on behalf of public health directives, health authorities’ recommendations, and supporting legal norms. Those dissenters have received strong criticism. Notwithstanding, they also provoked reflections and heated debates on the contours of fundamental rights and freedoms and their suspension or relativization during crises. Their situation is not new, however, and dissenters have often had to pay high prices for behaving in disaccord with conformist crowds, for contesting official policies and rules, or for going against majoritarian narratives. Dissenters are often seen as troublemakers, selfish, irrational, or even unpatriotic.